Cell Division Cycle-Associated Genes Are Potential Immune Regulators in Nasopharyngeal Carcinoma - Jiang, Danxian; Li, Yin; Cao, Jinxin; Sheng, Lianghe; Zhu, Xinhai; Xu, Meng (Frontiers in Oncology, 2022)
Background: Cell division cycle-associated (CDCA) gene family is essential to the cell cycle regulation. Numerous studies have illuminated that dysfunction of CDCA genes may not only lead to uncontrolled cell proliferation resulting in tumorigenesis but also influence immune cell infiltration in tumors. However, the role of the CDCA gene family on the prognosis and immune infiltration in nasopharyngeal carcinoma (NPC) still remains to be unclear. Methods: SBC human ceRNA array V1.0 was used to measure mRNA expression in three pairs of NPC tissues and nasopharyngitis tissues. The expression of CDCA8 was confirmed in an IHC microarray containing 130 NPC patients. Two external GEO cohorts were enrolled for further analysis. Prognosis analysis was performed using Kaplan-Meier method. Gene set enrichment analysis (GSEA) was applied to explore the potential mechanism of CDCA genes in NPC. The relationship between CDCA gene family and immune infiltration in NPC was evaluated using the Xcell tool. Results: CDCA genes were broadly up-regulated in NPC tissues compared to nasopharyngitis tissues, and high expression of CDCA3/5/8 indicated worse prognosis in NPC. Besides cell-cycle pathways, we found that CDCA3/5/8 were involved in multiple immune-related pathways. Overexpression of CDCA8 was strongly associated with less infiltration of CD8+ T cells and more infiltration of CD4+ Th1 cells and was negatively correlated with immune checkpoint blockade (ICB)-related genes. Conclusion: CDCA gene family was up-regulated in NPC and their expressions were associated with adverse prognosis. High expression of CDCA8 was associated not only with poor prognosis, but also with less immune infiltration and down-regulation of ICB-related genes in NPC.